Virulent Pseudomonas aeruginosa infection converts antimicrobial amyloids into cytotoxic prions. Issue 7 (15th May 2020) - Voth, Sarah; Gwin, Meredith; Francis, Christopher Michael; Balczon, Ron; Frank, Dara W.; Pittet, Jean‐Francois; Wagener, Brant M.; Moser, Stephen A.; Alexeyev, Mikhail; Housley, Nicole; Audia, Jonathon P.; Piechocki, Scott; et al.
Abstract: Pseudomonas aeruginosa infection elicits the production of cytotoxic amyloids from lung endothelium, yet molecular mechanisms of host‐pathogen interaction that underlie the amyloid production are not well understood. We examined the importance of type III secretion system (T3SS) effectors in the production of cytotoxic amyloids. P aeruginosa possessing a functional T3SS and effectors induced the production and release of cytotoxic amyloids from lung endothelium, including beta amyloid, and tau. T3SS effector intoxication was sufficient to generate cytotoxic amyloid release, yet intoxication with exoenzyme Y (ExoY) alone or together with exoenzymes S and T (ExoS/T/Y) generated the most virulent amyloids. Infection with lab and clinical strains engendered cytotoxic amyloids that were capable of being propagated in endothelial cell culture and passed to naïve cells, indicative of a prion strain. Conversely, T3SS‐incompetent P aeruginosa infection produced non‐cytotoxic amyloids with antimicrobial properties. These findings provide evidence that (1) endothelial intoxication with ExoY is sufficient to elicit self‐propagating amyloid cytotoxins during infection, (2) pulmonary endothelium contributes to innate immunity by generating antimicrobial amyloids in response to bacterial infection, and (3) ExoY contributes to the virulence arsenal of P aeruginosa through the subversion of endothelial amyloid host‐defense to promote a lung endothelial‐derived cytotoxic proteinopathy.